Revit 2022: Essential Training for Structure (Imperial). - Wing, Eric (linkedin.com, 2021)
Find out how to use Revit 2022 for structural engineering. Learn to design foundations, add framing and rebar, and plot drawings—using examples in imperial units (inches and feet).